Individual Differences in Activation of the Parental Care Motivational System: An Empirical Distinction Between Protection and Nurturance. Issue 8 (November 2018) - Hofer, Marlise K.; Buckels, Erin E.; White, Cindel J. M.; Beall, Alec T.; Schaller, Mark
Previous research reveals that individual differences in parental caregiving motives have implications (among both parents and nonparents) for a wide range of psychological outcomes. Here we report reanalyses of existing data sets to examine the extent to which these outcomes are uniquely predicted by two conceptually distinct factors underlying the parental caregiving motive: protection and nurturance . In doing so, we also psychometrically validate a brief self-report measure designed to efficiently assess individual differences in protection and nurturance. Results reveal that individual differences in parental protection uniquely predict a specific subset of attitudes and judgments (e.g., endorsement of restrictive parenting practices, harsher moral judgments of adults who violate social norms), whereas individual differences in parental nurturance uniquely predict a different subset of attitudes and judgments (e.g., nonparents desire to have children, preferences for committed romantic partners, more lenient moral judgments of children who violate social norms).